Pottery from the University of California, Berkeley excavations in the area of the Maški Gate (MG22), Nineveh, 1989-1990 - Wilkinson, Eleanor Barbanes, (Archaeopress Archaeology, 2022)
This work presents the pottery from the UC Berkeley excavations in 1989 and 1990. Nineveh is one of the longest occupied cities in the world, with a record of habitation extending back to at least the middle of the 7th millennium BC, continuing in an almost uninterrupted sequence through today. It was one of the major urban centres in which the fundamental features of modern civilisation first emerged. Its political and religious significance - particularly during its apogee as the capital of the Assyrian Empire in the late 8th and 7th centuries BC - secured its status as a legendary metropolis in history and literature.